343 The evolution of the nasopharyngeal bacterial community in beef steer calves from spring processing to 40. (7th December 2018) - McMullen, C; Orsel, K; Alexander, T; van der Meer, F; Plastow, G; Timsit, E
Abstract: The nasopharynx of beef cattle is host to a diverse population of bacteria, including those commonly associated with bovine respiratory disease. The composition of the nasopharyngeal bacterial community has been shown to play a role in bovine respiratory health. The objective of this study was to describe the evolution of the nasopharyngeal bacterial community from spring processing to 40 days after arrival at the feedlot. A total of 120 calves were enrolled from 3 farms (40 per farm) in southern Alberta, Canada. Guarded deep nasopharyngeal swabs were collected from each calf at the time of spring processing, feedlot arrival, and 40 days after feedlot arrival. Swabs from 114 animals and 11 negative control samples were available for 16S rRNA metagenomic sequencing. The V4 hypervariable region was targeted for paired-end sequencing at a read length of 2 x 250 base pairs using the Illumina ® MiSeq system. Sequencing reads are currently being processed using the DADA2 package in R to infer sample sequences exactly, allowing for identification of unique sequence variants. Sample communities will be analyzed in order to determine alpha- and beta-diversity. Additionally, sample communities will be clustered by taxonomy in order to analyze changes in community composition over time, including any potential patterns of change that may emerge. Preliminary bacterial culture results (Figure 1) show a general increase in Pasteurella multocida and Histophilus somni prevalence over time, while Mannheimia haemolytica prevalence fluctuates based on farm. A total of 23, 352, 909 sequencing reads were obtained from two separate sequencing runs (Phred quality scores of 35 and 36). This study includes a temporal component to microbiome evaluation, which is valuable as patterns of change in bacterial community composition can affect overall community stability. In turn, community stability can have an effect on respiratory health, a topic of significant importance to the beef industry.